PENINGKATAN EFISIENSI LOGISTIK UMKM MELALUI PENGELOLAAN RANTAI PASOK DAN INVENTORI BERBASIS TEKNOLOGI MUDAH - Jopinus Saragih; Adrian K. Tarigan; Idayanti Adelina Silalahi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This community service activity aims to improve logistics efficiency for MSMEs by enhancing supply chain management (purchasing–production–delivery) and inventory management (raw material & finished goods stock) using easily adopted technologies such as Google Sheets/online Excel, a simple stock application, transaction input forms, and dashboards. Common MSME issues include inaccurate stock levels, stockouts when order volumes are high, overstock tying up capital, messy manual records, reactive raw material ordering, and uncontrolled shipping costs. The interventions involve process auditing, establishing data standards and SOPs, implementing digital stock cards, setting practical reorder points, recording purchasing–consumption–sales activities, and monitoring logistics KPIs. The outputs include a simple inventory system, SOPs for warehousing and purchasing, stock and turnover dashboards, and impact reports (stock accuracy improvement, reduced stockouts, and cost savings).